PRÁTICAS DO ESPAÇO DOS GRUPOS DE JOVENS DO FAXINAL DOS TROJAN E DO LAGEADO DE BAIXO, MALLET/PR (1951-2005) - MIGON, GABRIELA (2021)
In this research, we studied the catholic groups for youngsters from the faxinal communities: Faxinal dos Trojan and Lageado de Baixo, located in the City of Mallet-PR. Specifically, between 1951 and 2005, we analyzed the space of formation and consolidation of such groups, the social conditions which led them to be considered youngsters and participants of the group, and the daily practices performed within it. This study was realized by means of oral reports, such as interviews, and through written material (book of minutes). From these documents, and anchored on the theoretical premises of Michel de Certeau regarding the history of the quotidian, we tried to demonstrate how such entities (re)invented themselves, how they made use of creativity and distortion regarding the rules set by the Latin, and Ukrainian rites, practiced, respectively, in these locals. When gathering to pray, these groups would bring on topics related to several promotional events, such as balls, parties, tournaments and trips. These events kept their religious aspect as well as parallel desires from groups’ participants, resulting in an absorption of religious rules arising from the youngsters themselves.